THE POLITICS OF THE SUNDANESE KINGDOM ADMINISTRATION IN KAWALI-GALUH (Paramita: Historical Studies Journal, 2017)
The focus of the study is the politics of the Sundanese Kingdom administration during a period when the power was centered in Kawali-Galuh. Astana Gede Kawali is a historical site that used to be the center of the Sundanese kingdom as solidly proven by the existence of a number of remaining historical plaques found in the site.  The study employed a four-step historical method that involved heuristics, criticism, interpretation, and historiography. The main concept underlying the study is Montesquieu’s Division of Power, also known as the Trias Politica. In general, the politics of the Sundanese kingdom administration remained unchanged despite the shifts of the administrative center to Galuh, Kawali, and Pakuan. The Sundanese kingdoms actually adopted a unique concept called Tri Tangtu di Buana, according to which administrative power was distributed triadically among Prebu, Rama, and Resi. The concept of Tri Tangtu Buana is similar to that of Montesquieu’s Trias Politica, which is commonly adopted by today’s modern states. Penelitian ini adalah tentang politik pemerintahan Kerajaan Sunda ketika kekuasaan berpusat di Kawali-Galuh. Astana Gede Kawali adalah salah satu situs peninggalan bersejarah yang merupakan bekas pusat pemerintahan Kerajaan Sunda Kawali-Galuh. Beberapa prasasti tentang Kerajaan Sunda yang ditemukan disana adalah bukti keras tentang itu. Metode yang digunakan dalam penelitian ini adalah Metode Sejarah yang didalamnya terdapat empat tahapan yaitu Heuristik, Kritik, Interpretasi dan Historiografi. Konsep yang digunakan dalam penelitian ini adalah Konsep Pembagian Kekuasaan Montesquieu yang terkenal dengan namaTrias Politica. Politik pemerintahan dalam kerajaan Sunda pada umumnya adalah sama walaupun pusat pemerintahannya berpindah pindah dari Galuh, Kawali dan Pakuan. Pemerintahan Kerajaan Sunda memiliki kekhasannya tersendiri dengan konsepnya Tri Tangtu di Buana yang didalamnya membagi kekuasaan pemerintahan dalam Prebu-Rama-Resi.Tri Tangtu di Buana ini memiliki kemiripan dengan pembagian kekuasaan yang terkenal dengan sebutan Trias Politica dari Montesquieu yang sekarang banyak digunakan dalam negara modern.